If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(7 + 5b) = 23 + b (7 * -7 + 5b * -7) = 23 + b (-49 + -35b) = 23 + b Solving -49 + -35b = 23 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -49 + -35b + -1b = 23 + b + -1b Combine like terms: -35b + -1b = -36b -49 + -36b = 23 + b + -1b Combine like terms: b + -1b = 0 -49 + -36b = 23 + 0 -49 + -36b = 23 Add '49' to each side of the equation. -49 + 49 + -36b = 23 + 49 Combine like terms: -49 + 49 = 0 0 + -36b = 23 + 49 -36b = 23 + 49 Combine like terms: 23 + 49 = 72 -36b = 72 Divide each side by '-36'. b = -2 Simplifying b = -2
| 12n=12 | | 3g^2(4g-7)= | | a/8-1=a/3-7/12 | | r+4.2=8.3 | | 4y^3+5y^2-6y^3-7y+19y^3= | | 19+7x=7+6(7x+2) | | 3x+15=123 | | 5x-11y=3 | | 4(d-2)=2(d+2) | | 9+7x=7x+6 | | 0.4n+2.7=5.1 | | -7n-26=-3(7+4n) | | 4(d-2)=(d+2) | | 2(4x+x)=15x-10 | | d+4=2+3d-.5 | | 3x-2+18x=18x+12+1 | | (4x-10)+(2x+20)=180 | | (3-11y)-(17+12y)= | | 2(4x+4)=15x-10 | | 31-7p=3(p+7) | | 5y(y^2-7y^3)= | | 3=-2-5k | | 1+7(3p+4)=15+7p | | 5-3z-18=z-1+8x | | 6(3x-5)-2(-6x+4)= | | -(-2x-8y-3)= | | 4x+9=x+4+8x | | 2x-3x=12 | | 2(9y-10)=40 | | -2y-10=5y+10 | | 3+-4a=11 | | 3x+3-x=2+x+2 |